Analysis of a solid oxide fuel cell and a molten carbonate fuel cell integrated system with different configurations - Jienkulsawad, Prathak; Saebea, Dang; Patcharavorachot, Yaneeporn; Kheawhom, Soorathep; Arpornwichanop, Amornchai (My University, 2018)
A solid oxide fuel cell with internal reforming operation is run at partial fuel utilization; thus, the remaining fuel can be further used for producing additional power. In addition, the exhaust gas of a solid oxide fuel cell still contains carbon dioxide, which is the primary greenhouse gas, and identifying a way to utilize this carbon dioxide is important. Integrating the solid oxide fuel cell with the molten carbonate fuel cell is a potential solution for carbon dioxide utilization. In this study, the performance of the integrated fuel cell system is analyzed. The solid oxide fuel cell is the main power generator, and the molten carbonate fuel cell is regarded as a carbon dioxide concentrator that produces electricity as a by-product. Modeling of the solid oxide fuel cell and the molten carbonate fuel cell is based on one-dimensional mass balance, considering all cell voltage losses. Primary operating conditions of the integrated fuel cell system that affect the system efficiencies in terms of power generation and carbon dioxide utilization are studied, and the optimal operating parameters are identified based on these criteria. Various configurations of the integrated fuel cell system are proposed and compared to determine the suitable design of the integrated fuel cell system.
Keywords: Design; Molten carbonate fuel cell; Recirculation; Solid oxide fuel cell; System configuration